The Hybridisation of Higher Education in Canada - Shale, Douglas (International Review of Research in Open and Distributed Learning, 2002)
Canada's postsecondary institutions are becoming increasingly involved with technology enhanced learning, generally under the rubric of distance education. Growth and activity in distance education stems from rapid developments in communication and information technologies such as videoconferencing and the Internet. This case study focuses on the use of new technologies, primarily within the context of higher education institutions operating in Canada's English speaking provinces. Capitalising on the interactive capabilities of "new" learning technologies, some distance education providers are starting to behave more like conventional educational institutions in terms of forming study groups and student cohorts. Conversely, new telecommunications technologies are having a reverse impact on traditional classroom settings, and as a result conventional universities are beginning to establish administrative structures reflective of those used by distance education providers. When viewed in tandem, these trends reflect growing convergence between conventional and distance learning modes, leading to the hybridisation of higher education in Canada.